Oblikovanje modela medpoklicnega sodelovanja medicinskih sester na področju zagotavljanja farmacevtske skrbi - Petrović, Marko (Obzornik zdravstvene nege, 2021)
Introduction: Interprofessional collaboration of nurses in pharmaceutical care is important in ensuring quality patient care. However, including nurses in pharmaceutical care opens up several issues related to their education and consequently, also their competencies to ensure effective pharmaceutical care. The aim of the study was to establish the viewpoints of doctors, pharmacists, and nurses, and about the role of nurses in interprofessional collaboration in pharmaceutical care in Slovenia. Methods: A descriptive interpretative method was used. A purposive quota sample included 24 participants: 8 doctors, 8 pharmacists and 8 nurses. Data were collected by semi-structured interviews. The obtained data were analysed using the content analysis method. Results: The study has showed that nurses have been performing tasks in pharmaceutical care and that they also see their role in further efforts of interprofessional collaboration. However, the results show that doctors and pharmacists are not in favour of nurses' potential professional competencies, which include pharmaceutical care. In particular, they draw attention to the knowledge that they consider nurses lack. They see a solution in the introduction of additional training in pharmacology. Nurses believe that they are mistreated or treated unequally in pharmaceutical care. Discussion and conclusion: Interprofessional collaboration of nurses in pharmaceutical care is highly significant and can bring positive results to treatment, but nurses should obtain additional knowledge, have a more prominent role in clinical trials and assume a more active role in these efforts.
Keywords: collaboration; farmacija; kakovost; medication handling; medicina; medicine; nursing care; pharmacy; quality; rokovanje z zdravili; sodelovanje; zdravstvena nega